2003
DOI: 10.1007/bf03173242
|View full text |Cite
|
Sign up to set email alerts
|

Co-construction of the representations of intelligence between mother and daughter: Developmental and differential approaches

Abstract: The problematic of this research concerns the question of the coconstruction of the representations of intelligence between mother and daughter, according to their age and contrasted socio-cultural environments. Our goal is to show that mothers and their daughters (for whom intelligence is a part of their everyday experiences, through their academic success or failure in particular) develop representations that are close and that the age of the daughters and their socio-cultural affiliation have an effect on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…The common sense theories concerning educational issues (and in particular with respect to intelligence and its development) have been investigated on several occasions, both in the theoretical field of social representations (e.g., Carugati, 1990a;Carugati & Selleri, 1998Carugati, Selleri, & Scappini, 1994;Constans & de Leonardis, 2003;Matteucci, 2003;Mugny & Carugati, 1985;Selleri, Carugati, & Scappini, 1995;, and implicit theories (e.g., Dweck & Legett, 1988;Dweck et al, 1993Dweck et al, , 1995. In particular, European investigators have expanded on the study of social representations of intelligence and its development, in teachers and parents, by assuming a link between representation and educational practices.…”
Section: The "Norm Of Effort" In the Classroom: An Analysis Of Behavimentioning
confidence: 99%
“…The common sense theories concerning educational issues (and in particular with respect to intelligence and its development) have been investigated on several occasions, both in the theoretical field of social representations (e.g., Carugati, 1990a;Carugati & Selleri, 1998Carugati, Selleri, & Scappini, 1994;Constans & de Leonardis, 2003;Matteucci, 2003;Mugny & Carugati, 1985;Selleri, Carugati, & Scappini, 1995;, and implicit theories (e.g., Dweck & Legett, 1988;Dweck et al, 1993Dweck et al, , 1995. In particular, European investigators have expanded on the study of social representations of intelligence and its development, in teachers and parents, by assuming a link between representation and educational practices.…”
Section: The "Norm Of Effort" In the Classroom: An Analysis Of Behavimentioning
confidence: 99%
“…Participants rated each of the 31 items for their extent of agreement or disagreement on a 7-point scale (1 = totally disagree, 7 = totally agree). A variety of themes formerly identified in literature or found in previous research findings were evaluated (Amaral, 1997;Constans & Leonardis, 2003;Faria & Fontaine, 1993;Matteucci, 2007;Miguel, Valentim, & Carugati, 2008;Miguel et al, 2010;Mugny & Carugati, 1985;1998Sternberg, 2004). Three main factors were yielded (Miguel et al, 2012): parents' role for the development of intelligence, emphasizing the provision of affective equilibrium and the setting of disciplinary practices (e.g., "the quality of affective relations between parents and children influences the development of intelligence", "without rules and discipline, the development of intelligence is compromised"); stimuli and incentives, alluring to incentives and external motivational strategies aimed at promoting intellectual development (e.g., "for the child to make progress, she has to be presented with challenges that stimulate her intellectually", "for the child to progress intellectually, it is essential to stimulate the development of reading habits"); and school, teachers and molding, which present severity and pressure on children as major factors for their intellectual development (e.g., "teachers' competence is the best assurance of the child's development of intelligence", "it is by contradicting the child when she is wrong that the development of intelligence is promoted").…”
Section: Development Of Intelligencementioning
confidence: 99%
“…Subjects answered a total of 31 items by indicating the extent of agreement or disagreement on a seven-point scale (1 = totally disagree, 7 = totally agree). The process which led to the construction of the questionnaire on the development of intelligence stemmed from previous stages of our research (Miguel, et al, 2008(Miguel, et al, , 2010, and from an extensive literature review (Amaral, 1997;Constans & Leonardis, 2003;Faria & Fontaine, 1993;Flament, 1999;Matteucci, 2007;Mugny & Carugati, 1985;Poeschl, 1998Poeschl, , 1999Poeschl, , 2001Sternberg, 1985Sternberg, , 2004Sternberg, et al, 1981). Overall, several dimensions related to the development of intelligence were included in the questionnaire: parent, teacher and peer role in the development of intelligence (e.g., "parents are the child's main model for the development of his/her own intelligence", "teachers' competence is the best assurance of the child's development of intelligence", "in a group of children working together, they will develop their intelligence better than if they each work by themselves"), stimuli and challenge (e.g., "for the child to make progress, he/she has to be presented with challenges that stimulate him/her intellectually"), social and biological determinism (e.g., "intelligence does not develop, it is a hereditary gift"),…”
Section: Development Of Intelligencementioning
confidence: 99%
“…Over the years, empirical research has identified a multiplicity of common sense definitions of intelligence, building it up as a matter of social controversy and as a polysemic and many-sided topic. More precisely, the relativism and multidimensionality of intelligence has been illustrated by particularly featured definitional components of intelligence, such as, for example, a matter of natural inequalities and giftedness, as an expression of social skills and adaptability, as cognitive ability to solve problems -especially in logics and mathematics -, as an ability to critically integrate knowledge and information, or as the capacity to interpret and express emotions (Amaral, 1997;Constans & Leonardis, 2003;Faria & Fontaine, 1993;Miguel, Valentim, & Carugati, 2008, 2010Poeschl, 1992;Raty & Snellman, 1997;Raty, Snellman, & Vornanen, 1993;Snellman & Raty, 1995;Sternberg, 1985;Sternberg, Conway, Ketron, & Bernstein, 1981). Furthermore, since Mugny and Carugati's (1985) seminal work on the social representations of intelligence and its development, research has systematically been confirming that psychosocial variables such as the shortage of information regarding the object of representation, the (un)familiarity with that object, the necessity of decision making and the maintenance of a positive social identity organize representations of intelligence, suggesting that the content of representations is directly linked to the activation of social roles and the salience of the object, leading individuals to modulate the opinions they express regarding intelligence (Amaral, 1997;Amaral, Vala, & Carugati, 2004;Carugati, Selleri, & Scappini, 1994;Miguel, et al, 2008Miguel, et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%